2023
DOI: 10.3390/agriculture13030684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zilpaterol Hydrochloride and Zinc Methionine on Growth, Carcass Traits, Meat Quality, Fatty Acid Profile and Gene Expression in Longissimus dorsi Muscle of Sheep in Intensive Fattening

Abstract: Zilpaterol hydrochloride (ZH) redistributes ingested energy and improves feed efficiency by increasing muscle mass and reducing fat in sheep and cattle carcasses in fattening; however, by increasing lipolysis and reducing intramuscular fat (IMF), it can affect meat quality in terms of the attributes of tenderness, juiciness, taste and color; in contrast, Zn methionine (ZM), due to its lipogenic effect, can improve meat marbling without affecting production efficiency. In the current study, 36 male Suffolk shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 72 publications
0
11
1
Order By: Relevance
“…In recent decades, research on feedlot ruminants has primarily focused on finding technologies that improve feed efficiency and growth rates during the fattening process [1,2]. The final phase of finishing is characterized by lower growth efficiency in lambs, mainly because their gain consists predominantly of fat rather than muscle [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, research on feedlot ruminants has primarily focused on finding technologies that improve feed efficiency and growth rates during the fattening process [1,2]. The final phase of finishing is characterized by lower growth efficiency in lambs, mainly because their gain consists predominantly of fat rather than muscle [3].…”
Section: Introductionmentioning
confidence: 99%
“…The final phase of finishing is characterized by lower growth efficiency in lambs, mainly because their gain consists predominantly of fat rather than muscle [3]. Thus, one of the main objectives during finishing is to augment the proportion or weight of muscles while decreasing the fat content in the carcass [1,2]. An alternative approach to achieve this goal is through the use of growth promoters, such as gluconeogenic precursors or β-adrenergic agonists (β-AA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies by [29,30], supplementing with ZH for 30 d can increase the toughness of the LM by 20.0 to 56.4%, which is consistent with our research showing a 21.5% increase in WBSF. However, other reports by [29,41] have not found any differences in WBSF between lambs treated with ZH and the control group. The final pH of the meat is a crucial factor in determining its quality, and lambs supplemented with ZH have been observed to produce meat with an elevated pH of 3.2 to 8.9% [42].…”
Section: Meat Qualitymentioning
confidence: 59%
“…β-agonists have been studied for their effect on the fatty acid profile of ruminants. In a study by [41] lambs treated with ZH showed an increase in polyunsaturated fatty acids in intramuscular fat. In their study on lambs, [44] found that administering Salbutamol, a β-agonist, led to a decrease in saturated fatty acids and an increase in total unsaturated fatty acids.…”
Section: Fatty Acidsmentioning
confidence: 94%